2015
DOI: 10.1038/ijir.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

The importance of psychosexual counselling in the re-establishment of organic and erotic functions after penile prosthesis implantation

Abstract: Although many studies about penile prosthesis implantation (PPI) have been published so far, only a small amount of them take into account patients and partners outcome in terms of satisfaction and erotic function. The aim of this study is to explore the value of psycosexual counselling in and the sexual and erotic function of penile prosthesis recipients. Thirty patients and their partners were randomised into two groups. In arm A (case group) patients and their partners underwent a multistep psychosexual cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…As one type of psychological intervention, sexual counseling can not only improve erectile function and sexual satisfaction but also increase treatment compliance in patients with ED caused by RP and penile prosthesis implantation, extended device application or hypospadias repair performed in childhood [69][70][71][72][73]. A meta-analysis has demonstrated that taking PDE5is to improve erectile function requires other comprehensive management, including sexual counseling, exercise and lifestyle changes [74].…”
Section: Attention To Psychological Factorsmentioning
confidence: 99%
“…As one type of psychological intervention, sexual counseling can not only improve erectile function and sexual satisfaction but also increase treatment compliance in patients with ED caused by RP and penile prosthesis implantation, extended device application or hypospadias repair performed in childhood [69][70][71][72][73]. A meta-analysis has demonstrated that taking PDE5is to improve erectile function requires other comprehensive management, including sexual counseling, exercise and lifestyle changes [74].…”
Section: Attention To Psychological Factorsmentioning
confidence: 99%
“…Uit een recente studie blijkt dat er een sterke positieve correlatie is met de tevredenheid van de man en de seksuele functie van de vrouw (gemeten met de Female Sexual Index scale) [14]. Het is dus belangrijk de partner bij de counseling te betrekken [15].…”
Section: Hoe Tevreden Is De Patiënt Met Een Erectieprothese? En Zijn unclassified
“…Al in de beginjaren van Udo Jonas werden patiënt en partner voor de implantatie uitgebreid seksueel gecounseld [22]. Het belang van seksuologische counseling voor het krijgen van een tevreden patiënt is logisch en aangetoond [14,15]. Onderwerpen die besproken moeten worden zijn: de achtergrond waartegen de wens om een prothese te laten plaatsen zich afspeelt, de motivatie voor een prothese, de medische, psychosociale en sociaal-relationele factoren die een rol spelen, mogelijke alternatieve behandelingen, de verwachtingen en of deze realistisch zijn en, tot slot, het omgaan met tegenslag bij een mechanische of esthetische onvolkomenheid of, in het ergste geval, infectie waarbij de prothese verwijderd moet worden [23].…”
Section: Urologische En Seksuologische Counselingunclassified
“…The modern prosthesis has been around for over 40 years and undergone numerous iterations. For patients refractory to medical therapies, including phosphodiesterase type 5 inhibitors, penile prosthesis placement is widely considered the gold standard surgical therapy ( 1 , 2 ). The IPP has evolved from the semi-rigid implant and two-piece inflatable prosthesis to the modern three-piece inflatable device, the “Cadillac” of available penile implants.…”
Section: Introductionmentioning
confidence: 99%